Role of noncoding RNA in the pathophysiology and treatment of intrauterine adhesion - Liu, Hui-Dong; Wang, Shao-Wei (Frontiers in Genetics, 2022)
Intrauterine adhesion (IUA) is one of the most common diseases of the reproductive system in women. It is often accompanied by serious clinical problems that damage reproductive function, such as menstrual disorder, infertility, or recurrent abortion. The clinical effect of routine treatment is not ideal, and the postoperative recurrence rate is still very high. Therefore, exploring the pathological mechanism of IUA and finding new strategies for the effective prevention and treatment of IUA are needed. The main pathological mechanism of IUA is endometrial fibrosis and scar formation. Noncoding RNA (ncRNA) plays an important role in the fibrosis process, which is one of the latest research advances in the pathophysiology of IUA. Moreover, the exosomal miRNAs derived from mesenchymal stem cells can be used to improve IUA. This paper reviewed the role of ncRNAs in IUA pathogenesis, summarized the core pathways of endometrial fibrosis regulated by ncRNAs, and finally introduced the potential of ncRNAs as a therapeutic target.